2008
DOI: 10.1103/physrevb.78.193102
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Verdet law in magnetophotonic crystals: Interrelation between Faraday and Borrmann effects

Abstract: The magneto-optical Faraday effect is studied in one-dimensional magnetophotonic crystals ͑MPCs͒. Mechanisms of a strong enhancement of the Faraday rotation at the edges of the photonic band gap are considered. High difference of refractive indexes of bismuth-substituted yttrium iron garnet ͑Bi:YIG͒ and SiO 2 layers provides a strong spatial localization of the optical field in Bi:YIG layers, which leads to manifold Faraday rotation enhancement at the photonic band edges. The Faraday rotation angle in the fini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 15 publications
3
29
0
4
Order By: Relevance
“…In the first case, for the frequencies at the bottom of the BG, the energy concentration in a high permittivity layer is greater than that for frequencies at the top of the BG. The direct Borrmann effect was confirmed in recent experiments [4]. In the case of the inverse Borrmann effect, the spatial distribution of energy is inverted and the electric field for frequencies at the bottom of the BG is mainly localized in the low permittivity layers.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…In the first case, for the frequencies at the bottom of the BG, the energy concentration in a high permittivity layer is greater than that for frequencies at the top of the BG. The direct Borrmann effect was confirmed in recent experiments [4]. In the case of the inverse Borrmann effect, the spatial distribution of energy is inverted and the electric field for frequencies at the bottom of the BG is mainly localized in the low permittivity layers.…”
Section: Discussionsupporting
confidence: 60%
“…3, it was theoretically shown that the spatial distribution of the electric field in a MPC strongly depends on both the field frequency and the material parameters of magnetic and non-magnetic layers. As a result, a possibility of a substantial enhancement of the Faraday effect as well as nonlinear magneto-optical effects in MPCs was predicted [3][4][5] and experimentally verified. 4 The dependence of optical and magneto-optical properties of PCs on the spatial distribution of electromagnetic waves inside PCs can be considered as an optical analog of the Borrmann effect, which manifests itself in anomalous absorption/transmission of x-rays in near-perfect crystals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For both substructures, the magnitude of FR has local maxima at the PBG edges that corresponded to the maxima in the transmittance spectra. The maximum angle of the FR for each substructure is at the long-wavelength edge of the PBG, which is a clear manifestation of the optical Borrmann eect in the articially stratied media [23]. Figure 2c shows the transmittance spectrum of the heterostructure SH.…”
Section: By 4 Transfer Matrix Formalismmentioning
confidence: 99%
“…Sensitivity of MO sensors can be enhanced by creating them on the base of the magnetophotonic crystals which allows one to enhance magneto-optical Faraday or Kerr eects at the edge of the photonic band gap or at the micro cavity mode [4]. Magnetoplasmonic nanostructures represent a special class of plasmonic nanostructures fabricated from magnetic metals (for example, from nickel, cobalt and iron or from composites of magnetic materials) and noble metals [58].…”
Section: Introductionmentioning
confidence: 99%